TEST FUSION IN ADULT FORAMINIFERA: A REVIEW WITH NEW OBSERVATIONS OF AN EARLY EOCENE NUMMULITES SPECIMEN - Ferràndez-Cañadell, Carles (J. Foraminiferal Res., 2014)
In foraminifera, so-called “double tests” usually arise due to abnormal growth originating mainly from twinning, but may also be caused by irregularities in the early chambers and by regeneration after test injury that modifies the direction of growth. A fourth cause of double tests has only rarely been reported: the fusion of the tests of two adult individuals. We studied an early Eocene Nummulites double test consisting of two adult individuals that fused after an extended period of independent growth. The specimen was studied using computed tomography with micrometric resolution (micro-CT) that allowed bi- and three-dimensional visualization of the internal structure. Before fusion each individual test had 30–36 chambers, which, by comparison with growth rates in recent nummulitids, implies at least three months of independent growth. After fusion, the compound test grew in two spirals that fused after about one whorl and then continued in a single spiral. To fuse their tests, either adult individuals have to be forced to do so or the allorecognition (ability to distinguish between self and another individual) mechanisms must fail. A possible explanation for the merged Nummulites tests in this study is forced fusion in attached individuals after surviving ingestion and digestion by a metazoan. Alternatively, environmental stress could lead to a failure of allorecognition mechanisms and/or foraminiferal motility. Once fused, subsequent growth seems to be determined mainly by the relative orientation of individual tests. In any case, the frequency in which adult fusion occurs remains unknown.